Tissue damage-induced axon injury-associated responses in sensory neurons: requirements, prevention, and potential role in persistent post-surgical pain - Rau, Kristofer K.; Harrison, Benjamin J.; Venkat, Gayathri; Donahue, Renée R.; Petruska, Sara E.; Hill, Caitlin E.; Taylor, Bradley K.; Petruska, Jeffrey C. (Frontiers in Pain Research, 2025)
Pain resulting from tissue damage, including surgical incision, is often only partially responsive to anti-inflammatory drugs, suggesting the contribution of a neuropathic mechanism. Tissue damage leads to expression in dorsal root ganglion (DRG) sensory neurons of activating transcription factor 3 (Atf3), a known injury-induced transcription factor. Atf3 expression is associated with sensitization of cellular physiology and enhanced amplitude/duration of a nociceptive reflex. It is unclear how tissue damage leads to these changes in the sensory neurons, but it could include direct damage to the tissue-innervating axons and inflammation-associated retrograde biochemical signalling. We examined the necessity and sufficiency of incision, inflammation, and axonal conduction for induction of Atf3 in response to skin incision in rat. Incision outside of a single dermatome, but close enough to induce inflammation inside the dermatome, was not sufficient to induce Atf3 expression in the corresponding DRG. Incision inside the dermatome led to strong expression of Atf3. An anti-inflammatory drug did not prevent this induction of Atf3. In a mouse model of repeated injury – a major etiological factor for chronic pain – a second plantar incision induced a significant extension in the duration of mechanical hypersensitivity as compared to a single plantar incision. This corresponded with a remarkable increase in Atf3 expression in a rat model of repeated incision. Together, these results suggest that damage to axons innervating the skin is both necessary and sufficient for induction of Atf3 expression in sensory neurons. This is dramatically increased by repeated injury. Further, pre-treatment of the nerves innervating the incised skin with bupivacaine, a local anesthetic commonly used to reduce surgical pain, did not prevent induction of Atf3, indicating that conduction of action potentials is not necessary for induction of Atf3. Closure of incision with surgical glue or treatment with polyethylene glycol, known to enhance membrane integrity after injury, reduced incision-associated regulation of Atf3, Growth-Associated Protein-43 (Gap43), and electrophysiological changes. We conclude that tissue damage-induced pain arises from a mix of Atf3-independent inflammation-related mechanisms and axonal damage-associated mechanisms and therefore requires a mix of approaches to prevent/treat persistent post-surgical pain.